Performance Evaluation of Hot Mix Asphalt using Recycled Aggregates and Polymer Modified Bitumen: Use of Polymer Modified Bitumen and Recycled Aggregates - Rehman, Zia ur; Salam, Abdus; Khan, Fayaz Ahmad; Badrashi, Yasir Irfan (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
The construction debris generated as a result of demolition of buildings produces a very ill effect on the esthetics of the surroundings. Instead of dumping this waste material if it could be put into some beneficial use this might add to the convenience of the municipality and can be regarded as a step towards the reduction of environmental hazard. This study aims at the utilization of this recycled aggregate for hot mix asphalt in combination with polymer modified bitumen. Several samples were prepared and tested containing 25%, 50% and 75% recycled aggregate along with virgin aggregate. They were compared with a control sample having 100% virgin aggregate. It was found that stability reduced with the increase in percentage of recycled aggregate similarly the percent air voids and VFA (voids filled with mineral aggregates) also increased but remained well above the minimum requirements mentioned in the AASHTO guidelines. The results indicated the suitability of recycled aggregates for the construction of new roads as they were fulfilling all the requirements of a suitable material to be utilized in the construction of pavements.